Global Labour‐Standards Advocacy by European Civil Society Organizations: Trends and Developments. (5th March 2013) - Fransen, Luc; Burgoon, Brian
Abstract In recent years, developments in intergovernmental organizations and transnational private governance organizations have created new opportunities and constraints for the promotion of global labour‐standards governance by civil society organizations (CSOs). This article describes how European CSOs (including trade union organizations and non‐governmental organizations (NGOs)) respond to these developments. It argues that European civil society is witnessing a threefold shift in priorities of labour‐standards advocacy: from pushing regulatory approaches to organizational capacity building; from corporate responsibility strategies focused on compliance to strategies focused on transparency; and from fair labour standards within the sustainable development agenda to a host of other issues. The overall result is that labour‐standards advocacy in general and private labour governance in particular are receiving less attention from European CSOs.